Trends of Early Marriage in Developing Countries: A Systematic Review - Suhariyati Suhariyati; Joni Haryanto; Ririn Probowati (Jurnal Ners, 2019)
Background: Early marriage is being increasingly recognized globally as a fundamental violation of human rights and a major obstacle to sustainable development. Early marriage occurs globally to varying degrees, especially in developing countries. The purpose of this article was to identify the determinants and impact of early marriage in developing countries.Method: A systematic search for studies published from 2014 up to 2019 was conducted via Scopus, Proquest, Elsevier, Science Direct, Sage Journal, SpringerLink and EBSCO. A total of 10 studies met the inclusion criteria. These were independently extracted by two reviewers.Result: Education and place of residence were the most commonly studied determinants of early marriage. Only a few of them reported results concerning the age difference between the spouses, access to media information and self-efficiency. Early marriage has a relationship with both the mother's and child's health. However, the significance of these associations was often small or inconsistent.Conclusion: This review summarizes the best available evidence for local policymakers and public health practitioners so then they can consider incorporating these findings into the development of intervention protocols for the prevention of early marriage.